2019
DOI: 10.3389/fonc.2019.01065
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Transcatheter Arterial Chemoembolization Plus Radiotherapy Combined With Sorafenib in Hepatocellular Carcinoma Showing Macrovascular Invasion

Abstract: The safety and efficacy of transcatheter arterial chemoembolization (TACE) plus intensity-modulated radiotherapy (IMRT) combined with sorafenib in hepatocellular carcinoma (HCC) showing macrovascular invasion (MVI) remain controversial. The records of 63 patients with HCC showing MVI, who underwent IMRT plus TACE combined with (28 participants; Group A) or without (35 participants; Group B) sorafenib from 2015 to 2018, were retrospectively reviewed to assess the progression-free survival (PFS), overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…of Patients (n) Survival Outcome OS Other Outcomes Adverse Events ≥ Grade 3 (%) Nakazawa et al (2014) 87 RT versus Sorafenib VP3–4 (PS 0–1; CP A) 57, 40 After PS matching n=28, 28 Median OS (months) 5.9 versus 4.3 After PS matching 10.9 versus 4.8, p =0.025 NA AST/ALT ↑ (0 versus 6), Appetite ↓ (0 versus 4), HFSD (0 versus 3) Leukocytopenia (1 versus 0) Fujino et al (2015) 91 3D CRT+HAIC (A) versus HAIC (B) VP3–4 (PS 0–1; CP A) 41, 42 Median OS (months) 12.1 versus 7.2 ORR (%) 56.1 versus 33.3 PPF (months) 5.8 versus 3.0 Leukopenia (12.2 versus 14.3), thrombocytopenia (12.2 versus 14.3), ALT/ AST ↑ (2.4 versus 4.8) Bilirubin ↑ (2.4 versus 2.4) Yoon et al, 2018 85 EBRT+TACE (A) versus sorafenib (B) VP3–4 (PS 0–1; CP A) 42, 42 OS: (A) 55.0 weeks; (B) 43.0 weeks A versus B RRR (%) at 24 weeks: 33.3 versus 2% TTP (weeks) 31.0 versus 11.7 PFS (%) at 12 weeks: 86.7% versus 34.3% ALT/AST ↑ (11.1 versus 6.8), HTN (0 versus 9.1), Diarrhea (2.2 versus 4.5), HFSD (0 versus 4.5) Kodama et al (2018) 121 RT+HAIC (A) versus Sorafenib (B) VP3–4 (PS 0–1; CP A) 36, 36 Median OS (months) 9.9 versus 5.3, P =0.002 PFS (months.) 3.9 versus 2.1, p =0.048 Leukopenia (8.3 versus 0) Thrombocytopenia (5.5 versus 0), ALT ↑ (2.7 versus 8.3), Bilirubin ↑ (2.7 versus 5.5), Diarrhea & fatigue (2.7 versus 13.9), HFSD (0 versus 5.5) Zhao et al (2019) 89 IM RT+TACE+Sorafenib (A) versus IM RT+TACE (B) VP2, VP3, VP4 (PS) 25 (2, 11, 12) versus 29 (1, 18, 10) Median OS (months) 19 v...…”
Section: Radiotherapymentioning
confidence: 96%
See 1 more Smart Citation
“…of Patients (n) Survival Outcome OS Other Outcomes Adverse Events ≥ Grade 3 (%) Nakazawa et al (2014) 87 RT versus Sorafenib VP3–4 (PS 0–1; CP A) 57, 40 After PS matching n=28, 28 Median OS (months) 5.9 versus 4.3 After PS matching 10.9 versus 4.8, p =0.025 NA AST/ALT ↑ (0 versus 6), Appetite ↓ (0 versus 4), HFSD (0 versus 3) Leukocytopenia (1 versus 0) Fujino et al (2015) 91 3D CRT+HAIC (A) versus HAIC (B) VP3–4 (PS 0–1; CP A) 41, 42 Median OS (months) 12.1 versus 7.2 ORR (%) 56.1 versus 33.3 PPF (months) 5.8 versus 3.0 Leukopenia (12.2 versus 14.3), thrombocytopenia (12.2 versus 14.3), ALT/ AST ↑ (2.4 versus 4.8) Bilirubin ↑ (2.4 versus 2.4) Yoon et al, 2018 85 EBRT+TACE (A) versus sorafenib (B) VP3–4 (PS 0–1; CP A) 42, 42 OS: (A) 55.0 weeks; (B) 43.0 weeks A versus B RRR (%) at 24 weeks: 33.3 versus 2% TTP (weeks) 31.0 versus 11.7 PFS (%) at 12 weeks: 86.7% versus 34.3% ALT/AST ↑ (11.1 versus 6.8), HTN (0 versus 9.1), Diarrhea (2.2 versus 4.5), HFSD (0 versus 4.5) Kodama et al (2018) 121 RT+HAIC (A) versus Sorafenib (B) VP3–4 (PS 0–1; CP A) 36, 36 Median OS (months) 9.9 versus 5.3, P =0.002 PFS (months.) 3.9 versus 2.1, p =0.048 Leukopenia (8.3 versus 0) Thrombocytopenia (5.5 versus 0), ALT ↑ (2.7 versus 8.3), Bilirubin ↑ (2.7 versus 5.5), Diarrhea & fatigue (2.7 versus 13.9), HFSD (0 versus 5.5) Zhao et al (2019) 89 IM RT+TACE+Sorafenib (A) versus IM RT+TACE (B) VP2, VP3, VP4 (PS) 25 (2, 11, 12) versus 29 (1, 18, 10) Median OS (months) 19 v...…”
Section: Radiotherapymentioning
confidence: 96%
“…Combinations of 3D CRT and HAIC, intermittent modulated radiotherapy (IM-RT) plus TACE and sorafenib, and 3D CRT plus portal vein stent placement along with TACE and sorafenib have reported better outcomes in the setting of HCC with VP3 and VP4 PVTT. [88][89][90] This combination provides survival benefits to HAIC non-responders as well. 91 A systemic review and meta-analysis comprising 25 studies (patients=2,577, randomized control trials (RCTs) =11, and non-RCTs=14), comparing TACE plus RT versus TACE alone in advanced unresectable HCC reported significantly better 1-, 2-, and 3-year survival among patients receiving TACE plus RT.…”
Section: Radiotherapymentioning
confidence: 99%
“…e maximum allowable point dose to the stomach and intestine was set to no more than 54 Gy, with the volume of organ receiving >45 Gy less than 15%, while the maximum permissible dose of the cord should be less than 45 Gy. e kidney volume receiving a dose of ≥20 Gy (V20) was less than 50% [10].…”
Section: Imrtmentioning
confidence: 99%
“…Brade et al [9] reported that the objective efficacy of sorafenib combined with external radiotherapy was not improved, whereas the adverse reactions were increased. Zhao et al [10] treated 63 HCC patients with macrovascular invasion (MVI) by using TACE plus IMRT combined with sorafenib and found an excellent safety profile and clinical efficacy. Here, we retrospectively analyzed the clinical data of 82 HCC patients with PVTT and evaluated the benefits, safety, and prognostic factors of IMRT combined with sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…The acceptance of sorafenib as the standard to which other newer agents and non-surgical interventions are compared has resulted in studies comparing its use as monotherapy with TACE plus external beam radiotherapy 59 and TACE plus intensity-modulated radiotherapy combined with sorafenib. 60 In the SARAH study, selective internal radiotherapy with yttrium-90 resin microspheres did not produce any survival benefit compared with sorafenib in locally advanced and inoperable HCC (median OS, 8.0 vs 9.9, p = 0.18), and did not meet the primary endpoint of OS. 61 Similarly, the addition of selective internal radiation therapy to sorafenib did not result in a significant improvement in OS compared with sorafenib alone.…”
Section: Approved First-line Agents For Hccmentioning
confidence: 91%